1984
DOI: 10.1002/ddr.430040505
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal mediation of the memory disorder in depression

Abstract: Many patients with major depression show deficits in information processing to a degree that parallels the severity of the mood disorder. Parallel findings of alteration in hormonal systems known to modulate memory functions suggest that the biological and cognitive changes described may be functionally linked. A specific goal for norepinephrine and the limbic hypothalamic-pituitary-adrenal axis is hypothesized and related to specific components of the alteration in information processing. The cognitive and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…There have been many reports about associations between memory performances and plasma glucocorticoid concentrations in Alzheimer's dementia, schizophrenia, and depression (Cohen et al, 1982;Reus, 1984;Hatzinger et al, 1995;Newcomer et al, 1998;Dong et al, 2004). Corticosterone, one of the glucocorticoids, is the most abundantly circulating hormone in the rat (Garcia-Bueno et al, 2007) and is produced by the stress-responsive hypothalamic-pituitary-adrenal axis (Newcomer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many reports about associations between memory performances and plasma glucocorticoid concentrations in Alzheimer's dementia, schizophrenia, and depression (Cohen et al, 1982;Reus, 1984;Hatzinger et al, 1995;Newcomer et al, 1998;Dong et al, 2004). Corticosterone, one of the glucocorticoids, is the most abundantly circulating hormone in the rat (Garcia-Bueno et al, 2007) and is produced by the stress-responsive hypothalamic-pituitary-adrenal axis (Newcomer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…NCAMs, membrane-bound glycoproteins of the immunoglobulin superfamily of adhesion molecules, play critical roles in morphogenesis, behavioral plasticity, and regeneration of the nervous system as well as in cell-cell interactions (Cremer et al, 1997;Schachner, 1997;Kiss et al, 2001;Sandi, 2004;Tsoory et al, 2008). Some researchers have reported associations between memory performance and depression (Cohen et al, 1982;Reus, 1984). Accordingly, it was emphasized that some antidepressants may be therapeutically effective against stress, improving cognitive functions and decreasing corticosterone levels (Shah et al, 2003;Wesolowska et al, 2006;Wright et al, 2006).…”
mentioning
confidence: 96%
“…Whilst it is possible that this disturbance arises quite simply as a result of lack of energy availability due to the drastically reduced food intake, it is also possible that the starvation-induced glucocorticoid alterations may play a role. There is evidence that glucocorticoids modulate central nervous system functions involved in stimulus perception and information processing (Carpenter and Gruen 1982;Reus 1984;Rubinow et al 1984;Wolkowitz et al 1990;Starkman et al 1992;Newcomer et al 1994;Lupien et al 1994;McEwan and Sapolsky 1995). Recent evidence suggests that these effects may be mediated, in part, through the hippocampus (Diamond et al 1989(Diamond et al , 1992(Diamond et al , 1994Pavlides et al 1993;McEwan and Sapolsky 1995).…”
Section: Introductionmentioning
confidence: 99%
“…HPA axis hyperactivity, usually measured by nonsuppression of plasma cortisol in the dexamethasone suppression test (DST), has been related to specific clinical features including anorexia, lethargy and sleep disturbance (Miller and Nelson, 1987). Some authors have also suggested a specific relationship with cognitive impairment (Reus, 1984;Oxenkrug and Gershon, 1986) and this work reviews the evidence in support of this hypothesis.…”
mentioning
confidence: 94%